(untitled) (Revista de História Regional, 2023)
This article intends to discuss the presence of Haitians an Africans employed in slaughterhouses in the West and Southwest regions of Paraná State during the period from 1990s to 2020s. The first idea organizing that proposal it presupposes that emigrate is not simply moving from one place to another place. But implies having positive expectations of finding work and improving life. It also presupposes losing ties of sociability, affective relationships, and the places where memory, patters and everything that constitutes the immigrants with this project were produced. Immigrants hope to find jobs and create strategies different from their patters, social practices and communities.